Exploring Engineering Managers' Perspectives on the Actions of Engineering Managers and Newly Hired Engineers During the New Engineers' Socialization Period. Issue 3 (3rd July 2022) - Dong, Yun; Ahn, Benjamin; Tobey, Uriah J.
Abstract: The purpose of this study is to explore engineering managers' perspectives on what actions they should perform to assist newly hired engineers and what proactive steps newly hired engineers should take during the onboarding/socialization period. In total, nine unique managers' actions and nine distinct new engineers' actions were identified by applying Morrison's socialization framework and interviewing seven engineering managers working in aerospace companies. This study offers practical actions that engineering managers and new engineers can apply during the socialization period, and it provides research design guidance that engineering managers can use to find additional actions attuned to their organizations/workgroups.